The effect of testing procedure on DSC measurements of Gd-Ti-Zr alloy using ZrO2 container - Turalska P.; Homa M.; Sobczak N.; Gazda A.; Wierzbicka-Miernik A.; Kaban I. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Differential Scanning Calorimetry (DSC) was applied to determine the critical temperatures of phase transformations in the Gd40Ti30Zr30 alloy (wt%). The comparative measurements were carried out using three types of measuring devices at a temperature RT- 1650°C in the same flowing gas (Ar, 99.9992%) but applying different testing procedures, which allowed obtaining dissimilar oxygen contents in the surrounding atmosphere. The high temperature interaction and reactivity taking place between molten alloy samples and ZrO2 container during DSC tests were evaluated by structural analysis of the resulting interfaces using alloy samples solidified inside the ZrO2 containers. The conducted research has demonstrated methodological difficulties accompanying measurements of the thermophysical properties of Gd-rich alloys by the container-assisted DSC method, particularly when the tests are performed in flowing argon atmosphere with significantly reduced oxygen content. Under non-oxidizing conditions, the degradation of ZrO2 container can take place during DSC testing because the selected Gd40Ti30Zr30 alloy reacts with the ZrO2 to form a continuous interfacial reaction product layer. Under slightly oxidizing conditions, the gadolinium oxide formed in situ on the alloy surface, plays the role of a barrier for direct contact between molten alloy and container and thus may suppress or even prevent the degradation of the container and its subsequent strong bonding with the holder.